Докажите тождества
а)(a-b)^2+(a-b)(b+a)=2a(a-b)
b)2(x+5)^2-2(5-x)(5+x)=4x(x+5)
c)2(c-3)^2-4(1-c)(c+1)=6(c-1)^2+8
d)3(m-4)(4+m)-3(2-m)^2=12(m-5)

1

Ответы и объяснения

2014-03-13T22:39:29+04:00
A) (a-b)^2+(a-b)(b+a)=2a(a-b)
       a^2-2ab+b^2+a^2-b^2=2a(a-b)
       2a^2-2ab=2a(a-b)
       2a(a-b)=2a(a-b)     
b)2(x+5)^2-2(5-x)(5+x)=4x(x+5)
    2(x^2+10x+25)-2(25-x^2)=4x(x+5)
     2x^2+20x+50-50+2x^2=4x(x+5)
     4x^2+20x=4x(x+5)
      4x(x+5)=4x(x+5)
c)2(c^2-6c+9)-4(1-c^2)=6(c-1)^2+8
    2c^2-12c+18-4+4c^2=6c^2-12c+6+8
    6c^2-12c+14=6c^2-12c+14
d)3(m-4)(4+m)-3(2-m)^2=12(m-5)
    3(m^2-16)-3(4-4m+m^2)=12(m-5)
     3m^2-48-12+12m-3m^2=12(m-5)
     12m-60=12(m-5)
     12(m-5)=12(m-5)

Мы выполнили преобразования левой части и получили в итоге правую часть